Estudo da relação entre as avaliações dos touchpoints na jornada do consumidor e a satisfação final do cliente - Pinheiro , Lucas Leal (2023)
The objective of this work is to study the relationship between touchpoints evaluations into customer journey and overall customer satisfaction. For this, 82 customers responses of satisfaction survey from an American technology company in Brazil were analyzed. This survey evaluated customer satisfaction at touchpoints along the customer journey and overall satisfaction using the Promoter Score indicator. A multiple linear regression was used to verify the relationship evaluated in each stage at the journey with the Promoter Score. As a result, a relationship model was created relating the evaluations of the main touchpoints and the customers' Promoter Score. The instrument obtained allows companies to develop efficiently actions plants focusing on touchpoints that contribute to the overall satisfaction of their customers.